Will climate change become the worst nightmare in public health? - Malida Magista (Berita Kedokteran Masyarakat (BKM), 2018)
Is it too early for Indonesia to worry about the threats of climate change to the health quality of its people? It is a common knowledge that climate change is the culprit of melting icebergs, dying polar bears, and worsened summer. However, almost no one has any concern about how climate change will increase the prevalence of mental illness, heart attacks, or even stunting. Nowadays, the earth climate has changed so much. The surface temperature and the sea level have increased steadily. the extreme weathers and disasters have occurred more intense and frequent. Then, how do these occurrences affect Indonesians’ health and wellbeing? Two diagrams were drawn to observe the connections of climate change-mental illness and climate change-the incidence of heart attacks. Mental illness and the incidence of heart attack were chosen as representatives of public health challenges in Indonesia. The variables of these diagrams were obtained from evidence-based research and reports. It is assumed that the extracted variables are heavily related to the socioeconomic and health conditions of Indonesians. Based on those diagrams, we cannot deny that climate change causes both direct and indirect damage to Indonesians’ health. Unfortunately, limited data and information about climate change and public health in Indonesia prohibit us to build a stronger argument about this problem. In the future, it is highly recommended that every public health professionals start to consider the effect of climate change into their interventions. A transdisciplinary approach between the Ministry of Health, the Ministry of Environment and Forestry, the Ministry of Social is urgently needed to start a comprehensive and progressive approach for Indonesians health and wellness.